Comprehensive Review of Sustainability Practices, Innovation, And Resource Management in Healthcare - AL Rashah, Rizg Ahmed S; Al rashah, Mohsen Abdullah; Al Rashah, Khaled Abdullah Hussin; Al Rashah, Shaker Mohsen R; Saleh, Ismail Ahmed; Al Shaiban, Mohammed Ali; Alrashah, Mohammed Ahmed; Alrashah, Mohammed Mohsen R; Alsarimi, Mazen Rizq Mohammed; Ishaq, Yaqoub Ishaq Ali Ibn; Al Musharraf, Nasser Hadi Nasser (Journal of Ecohumanism, 2024)
As it has been discovered, the shift in practice is as the healthcare industry seeks ways to incorporate sustainable practices, innovation, and resource optimization into its management. This paper focuses on the major activities, measures, and systems modern healthcare organizations have implemented to achieve sustainable development enhanced with better patient outcomes and optimized costs. Renewable energy integration on the grid, green technologies, strategies for waste minimization, and advances in healthcare processes are discussed in contemporary literature. It also reviews the obstacles to practice implementation, leadership’s contribution to sustainability, and the direction of sustainable healthcare practice. This review advises and informs research-based successful practices and the advantages of blending general business theories into healthcare by presenting case study findings.